Martial arts as sport and therapy - Burke, D. T.; Al-Adawi, S.; Lee, Y. T.; Audette, J. (The Journal of Sports Medicine and Physical Fitness, 2007)
The term Martial Arts is often used as general phrase to describe many of the combat arts, which have developed in eastern cultures over the past millennium. This paper reviews the Martial Arts from the original context of a trio of life skills. This trio includes the healing arts such as acupuncture, the self-exploration arts such as yoga, and the vital life skills such as meditation. As Martial Arts suggests the waging of combat, the origins of the most common combat arts are reviewed, with an overview of the difference between the hard and the soft styles. The arts developed not only in the eastern, but also in all parts of the world, with references of these types of combats arts in the writings of the ancient Egyptians and Greeks. In modern times, the combat arts are performed for both exercise and sport. A review of the injuries that occur, and the health benefits that might be expected are discussed. A review of the medical literature that demonstrates some of these health benefits is included, with Tai Chi Chuan as the most studied of these. The health benefits discussed include strengthen and self-efficacy of the elderly, reduced falls, increased exercise capacity, and benefits to the immune system and autonomic nervous system. The paper emphasized the breadth of the Martial Arts and the import of these to the sports and health community.